Karakteristik Personal Perempuan Nelayan dan Indeks Ketahanan Pangan Rumah Tangga di Lombok Barat - Hayati Hayati; Arifuddin Sahidu; Muktasam Muktasam (Universitas Mataram, 2023)
Domestic work carried out by fisherwomen is related to the implementation of household food security realization activities. The level of realization of household food security can be measured by calculating the household food security index which includes aspects of food availability, food access and food utilization. This achievement can be related to the personal characteristics of women as people who are responsible for implementing fisherman household food security activities. The research was aimed at analyzing: the personal characteristics of fisherwomen, the household food security index, and the influence of the personal characteristics of fisherwomen on the household food security index. The research was conducted in Batu Layar and Lembar Districts, West Lombok. Data were collected from as many as 60 respondents using interview techniques with fisherwomen using questionnaires and in-depth interviews with several key figures. Then the data were analyzed with a regression analysis test. The results of the analysis found that the personal characteristics of fisherwomen were characterized by the productive age group, the level of formal education was low, the non-formal education was moderate, the number of family members was classified as medium, and the motivation was classified as very high. Overall, the household food security index is classified as less food secure (90 percent) and food secure (10 percent). Overall, the personal characteristics of fisherwomen have no effect on the index of household food security. Partially, the components of age, formal education, and motivation have an influence on access to and utilization of food.